P-A12 Discordant HIV populations with discordant V3 tropism in CSF and Plasma: Implications for establishing HIV reservoirs. (April 2018) - Lange, Camille; Manion, Maura; Hullsiek, Kathy; Keele, Brandon; Highbarger, Helene; Meya, David; Boulware, David; Maldarelli, Frank
Abstract : CNS reservoirs of HIV are established early in infection and may be distinct from HIV populations in peripheral lymphoid organs, but the mechanisms responsible for compartmentalization are not well understood. To determine if HIV compartmentalization occurs during CNS infections, we investigated HIV populations in plasma and CSF in patients with active cryptococcal meningitis (CM). HIV infected patients with CM (N=73) from the COAT, ASTRO-CM studies, had lumbar punctures and phlebotomy. HIV RNA was quantified in plasma and CSF prior to initiating anti-CM or antiretroviral therapy. A subset (N=9) with CSF RNA >plasma RNA and another subset (N=9) with plasma RNA >CSF RNA underwent single genome sequencing (SGS) of HIV env from plasma and CSF. SGS of cellular DNA was also performed on a subset of patients (N=5) with lymphocytic pleocytosis. Nine hundred ninety-two SG sequences were obtained. Sequences were aligned and subjected to phylogenetic analyses, compartmentalization analyses (panmyxia) and cell tropism of the V3 loop in env for R5/X4 predictions (GENO2PHENO). Patients with CSF pleocytosis (WBC > 5 cells/ μ L), had higher levels of HIV in CSF than in plasma (p<0.05). In general, proportions of R5 and X4 variants in CSF and plasma were similar, but there was strong discordance in 4 patients, reflecting compartmentalization. Sensitive population analyses revealed viral compartmentalization between CSF and plasma (N=5). In patients with pleocytosis, HIV variants in CSF-derived cells were distinct from those in CSF, but were indistinguishable from PBMC-derived HIV. Overall, CSF compartmentalization of HIV was detectable in the majority of patients with CM. CSF pleocytosis does not contribute substantially to establishing HIV populations in CNS.